Food Security & Natural Resources, Review 2 by Sara Scherr, Ecoagriculture Partners - Scherr, Sara J. (2013)
Priorities for Public Sector Research on Food Security and Natural Resources, Review 2, Sara Scherr, Ecoagriculture Partners on April 12, 2013 at the Food Security Futures Conference in Dublin, Ireland.